2010
DOI: 10.1523/jneurosci.5574-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Lateral GABAergic Feedback onto Rod Bipolar Cells in Rat Retina

Abstract: -induced Ca 2ϩ release from intracellular stores via activation of ryanodine receptors. Furthermore, lateral nonreciprocal feedback is mediated primarily by GABA C Rs that are activated independently from receptors mediating reciprocal feedback inhibition. These results illustrate numerous physiological differences that distinguish GABA release at reciprocal and lateral synapses, indicating complex, pathway-specific modulation of RBC signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 81 publications
4
129
2
Order By: Relevance
“…Both GABA A -and GABA C Rs on RBC synaptic terminals can be activated by reciprocal feedback inhibition under various conditions (Chavez et al 2010;Eggers and Lukasiewicz 2006a,b;Hartveit 1999), but the subsynaptic localization of the two receptor types relative to each other remains unclear. EM indicates that both receptor subtypes are localized to RBC-A17 synapses (Fletcher and Wassle 1999), but double-label immunofluorescence data suggest that two subtypes are typically not colocalized at the same synapses (Fletcher et al 1998;Frazao et al 2007).…”
Section: Structural and Molecular Assessment Of The Microcircuitmentioning
confidence: 99%
See 3 more Smart Citations
“…Both GABA A -and GABA C Rs on RBC synaptic terminals can be activated by reciprocal feedback inhibition under various conditions (Chavez et al 2010;Eggers and Lukasiewicz 2006a,b;Hartveit 1999), but the subsynaptic localization of the two receptor types relative to each other remains unclear. EM indicates that both receptor subtypes are localized to RBC-A17 synapses (Fletcher and Wassle 1999), but double-label immunofluorescence data suggest that two subtypes are typically not colocalized at the same synapses (Fletcher et al 1998;Frazao et al 2007).…”
Section: Structural and Molecular Assessment Of The Microcircuitmentioning
confidence: 99%
“…Previous work has shown that, when reciprocal feedback is elicited by depolarizing a single RBC under whole cell voltage clamp, the feedback inhibitory postsynaptic current (IPSC) is mediated primarily by GABA A Rs (Chavez et al 2010;Singer and Diamond 2003). When synaptic activation of A17s is enhanced, either by blocking postsynaptic receptor desensitization or by augmenting release from RBCs, a GABA C R-mediated component emerges in the feedback IPSC (Chavez et al 2010;Hartveit 1999;Singer and Diamond 2003). The anatomical data presented in Fig.…”
Section: Structural and Molecular Assessment Of The Microcircuitmentioning
confidence: 99%
See 2 more Smart Citations
“…In the VIAAT KO, GABA A α1 at synapses onto BC axons is down-regulated whereas its expression on the dendrites is up-regulated. Furthermore, different ionotropic GABA receptor types (GABA A and GABA C ) clustered at nonoverlapping sites (33,34) but opposite the same presynaptic A17 amacrine cell bouton (35) are similarly downregulated in the VIAAT KO. Together, these observations imply that activity-dependent regulation of inhibitory receptors is input type-specific.…”
Section: Activity-dependent Regulation Of Inhibitory Receptor Expressionmentioning
confidence: 96%